2006
DOI: 10.1038/sj.mp.4001852
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-resistant anxiety disorders

Abstract: Several epidemiological studies confirmed that Anxiety Disorders as a group are the most prevalent psychiatric conditions in the United States. The importance of these conditions is underlined by the fact that they cause significant disability, poor quality of life, alcohol and drug abuse. Anxiety disorders are treatable conditions and respond to the front-line interventions such as serotonin reuptake inhibitors and cognitive behavioral therapy. However, only about 60% of patients respond to those treatments t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
184
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(192 citation statements)
references
References 67 publications
1
184
0
7
Order By: Relevance
“…Between one-third and two-thirds of anxiety patients are treatment-resistant or refractory (33), underscoring the need to develop more efficacious interventions. The present results highlight the potential utility of broad-spectrum (i.e., multisymptom) approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Between one-third and two-thirds of anxiety patients are treatment-resistant or refractory (33), underscoring the need to develop more efficacious interventions. The present results highlight the potential utility of broad-spectrum (i.e., multisymptom) approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety disorders, such as post-traumatic stress disorder, panic disorder, social phobia, specific phobia, and generalized anxiety disorder, comprise the most common psychiatric diseases in the United States (1). Mouse genetic studies have identified associations between glyoxalase 1 (Glo1) and anxiety-like behavior.…”
Section: Introductionmentioning
confidence: 99%
“…O processamento cognitivo dos transtornos ansiosos envolve a vulnerabilidade, pois os indivíduos tendem a superestimar o perigo e subestimar os recursos pessoais para lidar com essas situações e, a partir do momento em que ocorre um reconhecimento do perigo, ficam propensos a desenvolver mais pensamentos que mantêm a ansiedade (Bystritsky, 2006). Os próprios sintomas de ansiedade podem transformar-se em uma nova ameaça percebida, uma vez que prejudicam o desempenho do indivíduo em situação perigosa (Frewen et al, 2013).…”
Section: Introductionunclassified